ANALISIS BATIMETRI SUNGAI SERANG UNTUK MENDUKUNG PENGEMBANGAN INFRASTRUKTUR YOGYAKARTA - Ulinnuha, Hilmiyati; Faridatunnisa, Maritsa; Basith, Abdul (GEOID, 2020)
One criteria of a good infrastructure is to connect land, sea, and air transportation routes. To support good infrastructure in Yogyakarta, the development of Tanjung Adikarto port, located close to New Yogyakarta International Airport, is needed. Instead of having a good port infrastructure, Tanjung Adikarto Port experience sedimentation due to various factors. One of them is sediment carried by Serang River. Therefore, this study aims to analyze Serang River bathymetry and interpolate location of sedimentation in Serang River. The method of bathymetry analysis used is by testing the accuracy of the depth measurement data and interpolate the sedimentation location based on the transverse and longitudinal profile of the Serang River. In addition, Serang River tidal data analysis was also carried out and development problems in Tanjung Adikarto Port is also evaluated. The results of this study indicate that the tides still affect the dynamics of the Serang River up to about 1 km from the Tanjung Adikarto Port breakwater area. According to IHO standards, Serang River depth measurement data classified as Order 1, while sedimentation occur in the river bank area and around the entrance of Tanjung Adikarto Port. As for infrastructure development problem, Tanjung Adikarto Port sedimentation problem might be caused by breakwater conditions. However, this may requires further study.